Casa de discussão: uma análise da produção da norma a partir do campo do conselho de gestão do patrimônio genético - Pinto, Mônica da Costa (2012)
The present work intends to analyse the construction process of the norm in the field of access to genetic assets and the associated traditional knowledge, considering the legal acts inside CGEN – Genetic Assets Management Council – and their relationship with biotechnology science and traditional lore. The presented data was gathered through documental research, where meeting records and norms produced by CGEN and its Thematic Chambers, since the Council‘s creation until the year 2011, where examined. The access and benefit sharing started to be legaly adressed in an international scope at the Convention on Biological Diversity – CDB and, in Brazil, through the Provisional Measure MP 2.186-16/2001. These norms have emerged as concourse spaces for juridic, scientific, biotechnological and traditional knowledge discourses. In the biotechnology field it is treated according to Bourdieu (2010), whereas the traditional knowledge is considered inseparable from the lives of the communities who hold it (ALMEIDA, 2008). The norm, in this context, is presented as a discourse, according to Foucault (2011) and Miaille (2005), and as a conservative force for social inequalities (WOLKMER, 2003). The presented data suggest the reproduction of the general tendency inside CGEN to produce the norm as a discourse, pointing to a likely predominance of discourses related to biotechnology in detriment of those related to the defence of the interests of those detaining the traditional knowledge. Key-words: CDB, Genetic assets and associated traditional knowledge. CGEN. Norm. Discourse.